Newly acquired Onchocerca volvulus filariae after doxycycline treatment - Specht, Sabine (Springer-Verlag, 2009)
Despite successful mass drug administration and vector control programs, the nematode Onchocerca volvulus is far from being eradicated. Therefore, new long-term sterilizing or macrofilaricidal drugs are needed. The depletion of Wolbachia endobacteria using doxycycline leads to long-term sterilizing effects and macrofilaricidal activity against female filariae of more than 60%. The worms die or degenerate 18–27 months after doxycycline. However, during this time patients may be exposed to new infections. We evaluated these newly acquired worms in onchocercomas of doxycycline-treated patients in relation to transmission using morphology, histochemistry, and immunohistology. On an average, 10% of the female filariae had been newly acquired per year in the treated groups. Our observations showed: (a) Sixty-three of 68 newly acquired worms harbored many intact Wolbachia, whereas none of the other surviving worms contained many bacteria. (b) Higher percentages of dead filariae than originally reported were calculated, when the new worms were excluded, indicating a stronger macrofilaricidal activity than previously reported. The difference was significant for female filariae after doxycycline treatment for 6 weeks. (c) Only newly acquired worms presented normal embryogenesis and microfilariae production after sufficient treatment. We conclude that newly acquired filariae have to be considered when evaluating drug efficacy in onchocerciasis.